Selenomethionine supplementation reduces lesion burden, improves vessel function and modulates the inflammatory response within the setting of atherosclerosis - Yunjia Zhang; Siân P. Cartland; Rodney Henriquez; Sanjay Patel; Bente Gammelgaard; Konstantina Flouda; Clare L. Hawkins; Benjamin S. Rayner (Redox Biology, 2020)
Atherosclerosis is a chronic inflammatory disease of the vasculature characterised by the infiltration of activated neutrophils and macrophages at sites of damage within the vessel wall, which contributes to lesion formation and plaque progression. Selenomethionine (SeMet) is an organic form of selenium (Se), an essential trace element that functions in the regulation of the immune response by both bolstering the endogenous thioredoxin and glutathione antioxidant defence systems and by directly scavenging damaging oxidant species. This study evaluated the effect of dietary SeMet supplementation within a high fat diet fed apolipoprotein E deficient (ApoE−/-) mouse model of atherosclerosis. Dietary supplementation with SeMet (2 mg/kg) increased the tissue concentration of Se, and the expression and activity of glutathione peroxidase, compared to non-supplemented controls. Supplementation with SeMet significantly reduced atherosclerotic plaque formation in mouse aortae, resulted in a more stable lesion phenotype and improved vessel function. Concurrent with these results, SeMet supplementation decreased lesion accumulation of M1 inflammatory type macrophages, and decreased the extent of extracellular trap release from phorbol myristate acetate (PMA)-stimulated mouse bone marrow-derived cells. Importantly, these latter results were replicated within ex-vivo experiments on cultured neutrophils isolated from acute coronary syndrome patients, indicating the ability of SeMet to alter the acute inflammatory response within a clinically-relevant setting. Together, these data highlight the potential beneficial effect of SeMet supplementation as a therapeutic strategy for atherosclerosis. Keywords: Atherosclerosis, Selenomethionine, Inflammation, Glutathione peroxidase